Informal education in the city of La Coruña (Journal of Parents and Teachers, 2026)
This volume presents programmes of cultural and educational activities organised by the municipal education service for the 1989–1990 academic year. It thus provides a forum for reflection on the educational, social and methodological value of drama for children and young people, both within and outside Galicia. We can also find a variety of examples from professional theatre companies, teachers and drama workshops from different regions.
Keywords: Urban environment; socialisation; community learning